Morphological characterization of grapevine varieties for Pisco production under conditions of the middle zone of the Ica valley, Peru - Cáceres, H. (2017)
This work consists in the morphological characterization of eight Pisco grapes varieties “Torontel, Italia, Mollar, Quebranta, Negra criolla, Albilla, Moscatel and Uvina” cultivated in the CITEagroindustrial, based on the International Organization of Vine and Wine (OIV) list of descriptors for vine varieties and Vitis species, version 2009. Some ampelographic characters such as berry color and shape during the phenological stage are general knowledge, however the 56 descriptors in different phenological stages highlight differences. Therefore, the description of the varieties provides a greater precision to the characterization and serves as a guide to the producers of Pisco and producers of grapes, for a simple and correct identification of their plants in the field, avoiding the confusion that currently exists in the Identification of the different varieties, such as homonymy and incorrect identification.